Relationship External Factors with Internet Addiction in Adolescent Age 15-18 Years - Masdum Ibrahim; Suryani Suryani; Aat Sriati (Faculty of Nursing Universitas Padjadjaran, 2019)
The internet is one form of evolution in the development of communication and technology that affects humans. One result of the internet is a significant change in the pattern of primary social interactions between individuals. The convenience provided by the internet indirectly causes individuals to have high levels of addiction to the internet and tend to show symptoms of addiction. In Indonesia, internet addiction is mainly found in groups of adolescents aged 15-22 years. This study aims to determine the relationship of external factors: academic stress, family attachments and peers with internet addiction in high school adolescents aged 15-18 years. The study design was carried out using a correlational research design with a cross sectional approach. Respondents who contributed in this study were 97 senior high school students. With sample selection, random sampling is done. The statistical test used was chi-square. The results of this study prove that academic stress has a significant relationship with internet addiction value X2 = 7.91 and P = 0.019 <0.05. Family attachments did not have a relationship with internet addiction, the value of X2 = 0.046 and P 1,000> 0.05 and peers did not have a relationship with internet addiction X2 = 0.241 and P = 0.657. Based on the results of this study, it can be said that the school through the school committee to share information or share about the problem of teenagers who experience academic stress, internet addiction, impact and how to overcome them also evaluate the learning process.